Cambridge IGCSE computer science - Watson, David; Williams, Helen (Hodder Education, 2015)
Endorsed by Cambridge International Examinations.Develop your students computational thinking and programming skills with complete coverage of the latest syllabus from experienced examiners and teachers. - Follows the order of the syllabus exactly, ensuring complete coverage- Introduces students to self-learning exercises, helping them learn how to use their knowledge in new scenariosAccompanying animation files of the key concepts are available to download for free online. See the Quick Links to the left to access.This book covers the IGCSE (0478), O Level (2210) and US IGCSE entry (0473) syllabuses, which are for first examination 2015. It may also be a useful reference for students taking the new Computer Science AS level course (9608).